Advances in Pediatric Critical Care Research in India - Bhalala, Utpal; Bansal, Arun; Chugh, Krishan (Frontiers in Pediatrics, 2018)
Over last 2 decades, there has been a significant progress made in the field of pediatric critical care in India. There has been complementary and parallel growth in the pediatric critical care services in India and the number of pediatric critical care providers who are either formally trained in India or who have returned to India after their formal training abroad. The pediatric critical care community in India has recognized obvious differences in profiles of critical illnesses and patients between Indian subcontinent and the West. Therefore there is a growing interest in generating scientific evidence through local research which would be applicable to critically ill children in Indian subcontinent. This article focuses on advances in pediatric critical care research in India and its future directions.